2002
DOI: 10.1046/j.1439-0272.2002.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lepidium meyenii (MACA) on sexual desire and its absent relationship with serum testosterone levels in adult healthy men

Abstract: This study was a 12-week double blind placebo-controlled, randomized, parallel trial in which active treatment with different doses of Maca Gelatinizada was compared with placebo. The study aimed to demonstrate if effect of Maca on subjective report of sexual desire was because of effect on mood or serum testosterone levels. Men aged 21-56 years received Maca in one of two doses: 1,500 mg or 3,000 mg or placebo. Self-perception on sexual desire, score for Hamilton test for depression, and Hamilton test for anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
135
1
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 31 publications
(30 reference statements)
7
135
1
14
Order By: Relevance
“…These findings support previous in vivo investigations into the effect of maca consumption on sexual desire in humans and rats [2,4]. However, Gonzales et al (2002) did not encounter an increase in sexual desire until 8 weeks of treatment. In this study, participants were subjectively asked to simply report if treatment diminished, did not change, increased mildly or increased moderately to highly sexual desire.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings support previous in vivo investigations into the effect of maca consumption on sexual desire in humans and rats [2,4]. However, Gonzales et al (2002) did not encounter an increase in sexual desire until 8 weeks of treatment. In this study, participants were subjectively asked to simply report if treatment diminished, did not change, increased mildly or increased moderately to highly sexual desire.…”
Section: Discussionsupporting
confidence: 90%
“…Consumption of maca has tentatively been linked with an increase in testosterone in some [8] but not all [4] studies. Pre-competition elevated hormone levels have been associated with 'the home advantage' and thus increased aggression and performance in team invasion games such as association football [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial research has focussed on a possible role for Maca in improving male fertility [7][8][9][10][11][12][13][14] with emerging evidence that Maca may improve sperm production and quality 7 . Although few studies have as yet examined the effect of Maca in women, data from oophorectomized rats, suggests that Maca can improve bone mass and restore trabecular network in the lumbar vertebrae, findings relevant to the high risk of osteoporosis many women face after menopause 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Maca, like ginger, is a powerful adaptogene, which improves the body ability to adapt to complicated and stressful situations. Scientific studies have shown that Maca improves memory and neurotransmitter function, increases the amount of oxygen in the blood and enhances libido [5][6][7][8]. Maca alkaloids positively effect hypothalamus and adrenal glands, and this provides energy, and increases vitality [7; 9].…”
Section: Introductionmentioning
confidence: 99%